2015
DOI: 10.1016/j.jaci.2014.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early-life exposures on food sensitization and food allergy in an inner-city birth cohort

Abstract: Rationale Previous data suggest that food allergy may be more common in inner-city children; however, these studies have not collected data on both sensitization and clinical reactivity, or early life exposures. Methods Children in the URECA birth cohort were followed through age 5 years. Household exposures, diet, clinical history, and physical examinations were assessed yearly; specific-IgE to milk, egg, and peanut were measured at 1, 2, 3, and 5 years. Based on sensitization (IgE≥0.35 kU/L) and clinical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
72
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 39 publications
2
72
0
2
Order By: Relevance
“…According to the primary model, this was also true for eczema. In keeping with our results, the Urban Environment and Childhood Asthma study reported no association between food allergy (diagnosed according to IgE levels ≥0.35 and a history suggestive of food allergy) and wheeze in the first 2 years life,27 and in the Tuscon Children’s Respiratory Study, eczema was not a risk factor for transient early wheezing 2. A likely explanation for these findings is that early childhood wheeze is predominantly driven by respiratory tract infections rather than atopy.…”
Section: Discussionsupporting
confidence: 87%
“…According to the primary model, this was also true for eczema. In keeping with our results, the Urban Environment and Childhood Asthma study reported no association between food allergy (diagnosed according to IgE levels ≥0.35 and a history suggestive of food allergy) and wheeze in the first 2 years life,27 and in the Tuscon Children’s Respiratory Study, eczema was not a risk factor for transient early wheezing 2. A likely explanation for these findings is that early childhood wheeze is predominantly driven by respiratory tract infections rather than atopy.…”
Section: Discussionsupporting
confidence: 87%
“…It is thought that multiple factors, such as differences in pathogen exposure during childhood, the characteristics of the host's microbiome, and many other environmental influences, as well as genetic background and the nature and frequency of exposure to potential allergens, can contribute to the variation in individual susceptibilities to develop clinical allergies 67-70 . Here we compared the resistance of C57BL/6 and BALB/c mice to RVV or BV following one versus two sublethal exposures to the same venom.…”
Section: Discussionmentioning
confidence: 99%
“…Considering these limitations, there is insufficient data at this time to suggest whether breast-feeding is a protective factor in the development of food allergy. 95,119,120 …”
Section: The Influence Of the Microbiome In Food Allergymentioning
confidence: 99%